Pengaruh Suhu Dan Kelembapan Terhadap Denyut Nadi Operator Kamar Mesin Di Pabrik Kelapa Sawit PT XYZ - Mahyunis, Mahyunis; Raja, Padamulia; Lubis, M Fahmi Fatan (CV. IRA PUBLISHING, 2024)
A palm oil mill has several workstations involved in processing palm oil into Crude Palm Oil (CPO). According to the Indonesian Minister of Manpower Decree No. 5 of 2018, the ideal temperature in industrial work areas is 23-26˚C. This study aims to measure the temperature and humidity in the engine room, as well as the operators' pulse rates during rest and work, using a quantitative method. Measurements were taken at 09:00, 12:00, and 15:00 at four observation points. The results showed that the highest temperature reached 32.75˚C, exceeding the standard limit, with an average humidity of >80%, also surpassing the industrial standard (40-60%). These conditions indicate the need for improved ventilation and the use of devices such as exhaust fans and dehumidifiers to reduce temperature and humidity. The installation of real-time temperature and humidity control devices is proposed to enhance working conditions in the engine room.